Variation in Growth Patterns and Condition Factors of Fringe scale sardinella (Sardinella fimbriata) Based on the Moon Phase in Takalar Waters, Makassar Strait - Irsandi, Irsandi; Kantun, Wayan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
This study was conducted from March to May 2025 in the waters of Takalar, Makassar Strait. This study used the observation and sampling method at the Takalar Beba Fish Landing Place. The data taken were in the form of fish length and fish weight to be used to obtain growth patterns and condition factors and the results obtained were analyzed descriptively narratively. The results showed that the number of catches of Fringe scale sardinella l during the bright moon phase was 1,389 fish, while in the dark moon phase it was 337 fish. These results indicate that the size distribution in the bright moon phase ranges from 10-14.5 cm (12.002 ± 0.972 cm) with a weight ranging from 10-25 g (17.070 ± 3.676 g) and the dark moon ranges from 11-14 cm (12.047 ± 0.938 cm) with a weight ranging from 12-25 g (16.727 ± 3.489 g). Fringe scale sardinella in both moon phases have a negative allometric growth pattern (b < 3), which is 2.2148 in the bright moon and 2.0683 in the dark moon. The relative condition factor value ranges from 0.681–1.059 (1.004 ± 0.095) in the bright moon and 1.108–1.195 (1.004 ± 0.088) in the dark moon. The negative allometric growth pattern is an indication of high fishing pressure with the utilization of Fringe scale sardinella in the bright moon phase as a more effective time.